Eco-friendly synthesis of magnetic Pd/NiFe₂O₄/chitosan nanobiocatalyst for enhanced degradation of Congo red dye under sunlight irradiation - Mohammad Panahimehr; Mehdi Hosseini; Ayyub Mojaddami; Shahnaz Karamipour (Results in Chemistry)
In this research, the magnetic nanobio photocatalyst Pd/NiFe₂O₄/chitosan was synthesized using a green synthesis method. The characterization of this photocatalyst was carried out through several techniques including FT-IR, XRD, VSM, TEM, FESEM, and EDS. FESEM images confirm that the particle morphology is rice-like and uniform. Also, the TEM image confirms the incorporation of palladium in the chitosan matrix with an average particle size of 18 nm. Optical properties investigation using the Tauc diagram showed that the band gap of the photocatalyst is 2.52 eV, placing it within the visible light range. The performance of this photocatalyst for the degradation of the organic dye Congo red under sunlight irradiation was evaluated and the results showed that this photocatalyst was able to degrade the dye with an efficiency of 94.9 % within 30 min. Another outstanding feature of this photocatalyst was its recyclability with magnetic separation and reusability. After five consecutive cycles, the photocatalyst was easily separated by an external magnet and maintained its performance without significant structural changes. The results of this research demonstrate that Pd/NiFe₂O₄/chitosan acts as a highly efficient and stable photocatalyst, capable of degrading organic pollutants under ambient conditions. The integration of chitosan biopolymer into the nanophotocatalyst's design represents a key strength of this study, serving dual roles in facilitating eco-friendly synthesis and enhancing environmental compatibility. Furthermore, the incorporation of palladium effectively suppresses electron-hole recombination while narrowing the band gap, thereby improving photocatalytic efficiency.